2019
DOI: 10.14740/jmc3246
|View full text |Cite
|
Sign up to set email alerts
|

Nodular Pulmonary Sarcoidosis

Abstract: Nodular sarcoidosis is a rare form of pulmonary sarcoidosis comprising 4% of lung involvement in this disease. It usually affects African American women with a mean age of 35 years. It presents with constitutional symptoms associated with chest imaging findings of multiple or solitary lung nodules. In our case we present a 38-year-old woman who had chronic productive cough associated with fever and dyspnea for 1 month. She had course of antibiotics without improvement in her symptoms. Chest imaging showed mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…An observational study on 33 cases of nodular sarcoidosis revealed that 18% of patients presented with a solitary mass or nodule [ 4 ]. Although large pulmonary masses are extremely rare, nodular sarcoidosis of size up to 7.5 cm have been described [ 7 ]. Lesions predominately involve the upper lobes and are generally located in the periphery of the lungs, with ill defined, irregular borders [ 4 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…An observational study on 33 cases of nodular sarcoidosis revealed that 18% of patients presented with a solitary mass or nodule [ 4 ]. Although large pulmonary masses are extremely rare, nodular sarcoidosis of size up to 7.5 cm have been described [ 7 ]. Lesions predominately involve the upper lobes and are generally located in the periphery of the lungs, with ill defined, irregular borders [ 4 , 8 ].…”
Section: Discussionmentioning
confidence: 99%